A comparison of plasma glutamine concentration in athletes from different sports - Hiscock, N.; MacKinnon, L. T. (Medicine & Science in Sports & Exercise, 1998)
PURPOSES: The purposes of the current investigation were to compare resting plasma glutamine concentration in athletes from different sports and to determine the relationship between resting plasma glutamine concentration and dietary protein intake. METHODS: Resting plasma glutamine concentration was measured in five groups of eight distance runners, competitive swimmers, cyclists, powerlifters, and nonathletes. Dietary protein intake of each subject was measured (g.d-1 and g.kg-1.d-1). RESULTS: Plasma glutamine concentration was significantly different between sports (P = 0.000, ANOVA) with mean plasma glutamine concentration of cyclists significantly higher than in all other groups, and mean plasma glutamine concentration of powerlifters and swimmers significantly lower than in cyclists and nonathletes (P < 0.05, post hoc analysis). There was no significant relationship between plasma glutamine concentration and total dietary protein intake when expressed as g.d-1 (r = 0.11, P > 0.05); however, plasma glutamine concentration and dietary protein relative to body mass (g.kg-1.d-1) were significantly inversely correlated (r = -0.37, P = 0.007). CONCLUSIONS: These data suggest that resting plasma glutamine concentration may vary between sports, possibly due to metabolic demands of the different sports; dietary factors may also affect plasma glutamine concentration.